Representasi Kemiskinan Dalam Film Turah - Utari Rachmawati; Ike Desi Florina; Inas Sany Muyassaroh (Badan Penerbit STIEPARI Press, 2022)
Representation of poverty in Turah movie explained through dialogue, language, symbol, image, expression which contain in the scene. Each scene in Turah movie is analyzed using Roland Barthes's semiotics, through denotation, connotation and myth as the process. This study method used a qualitative descriptive approach, with the aim of the research that is find out representation of poverty in